Metallohelices stabilize DNA three-way junctions and induce DNA damage in cancer cells - Malina, Jaroslav; Kostrhunova, Hana; Scott, Peter; Brabec, Viktor (Nucleic acids research, 2023)
DNA three-way junctions (3WJ) represent one of the simplest supramolecular DNA structures arising as intermediates in homologous recombination in the absence of replication. They are also formed transiently during DNA replication. Here we examine the ability of Fe(II)-based metallohelices to act as DNA 3WJ binders and induce DNA damage in cells. We investigated the interaction of eight pairs of enantiomerically pure Fe(II) metallohelices with four different DNA junctions using biophysical and molecular biology methods. The results show that the metallohelices stabilize all types of tested DNA junctions, with the highest selectivity for the Y-shaped 3WJ and minimal selectivity for the 4WJ. The potential of the best stabilizer of DNA junctions and, at the same time, the most selective 3WJ binder investigated in this work to induce DNA damage was determined in human colon cancer HCT116 cells. These metallohelices proved to be efficient in killing cancer cells and triggering DNA damage that could yield therapeutic benefits.
Keywords: železnaté sloučeniny; Ferrous Compounds; Nucleic Acid Conformation; lidé; DNA Damage; konformace nukleové kyseliny; DNA; nádory; Humans; Neoplasms; poškození DNA